Multi Objective Programming Approach for Watershed Planning - A Case Study - Paul, J.C.; Mishra, S.B.; Ghal, G.C. (Journal of Soil and Water Conservation, 2022)
A watershed managmenet planning study is carried out with the help of multi-objective programming approach and analysed with STEP method. The selected watershed is Barapita nallah miniwatershed, which lies in Bhubaneswar block of Khurda district of Orissa having a total geographical area of 1442.42 ha and treatable area of 912.63 ha. In the multi-objective approach a compromise solution is derived from a set of optimal solutions by the preference of the Decision Maker (planner) in the interactive process. In this method steps are taken for optimal utilization of land, water and human resources for optimization of objectives like food, fodder, fuel wood, net income generation, labour employment generation and runoff water augmentation. From the proposed plan the benefit cost ratio is found to be 1.3:1 and the cropping intensity is 142% (Kharif 86% and Rabi 56%). The net benefit for the proposed planning is Rs. 13,921.35 x 103 as compared to Rs. 5,025 x 103 for the existing practice, which is 177% higher than the existing one. Also various soil and water conservation structures are proposed to fulfill the need of the area and to augment water for the utilization for irrigation in dry seasons.